(untitled) (Journal of Nepal Geological Society, 2024)
This study presents a detailed geological mapping at a 1:25,000 scale, aiming to establish the stratigraphy and geological structures of Khutti Khola Watershed, Lahan and Dhangadhi Municipalities, Siraha district. The Sub-Himalayan rock sequence of the study area is divided into the Lower Siwalik, Middle Siwalik, and Upper Siwalik units. The Middle Siwalik is further subdivided into the Middle Siwalik 1 and the Middle Siwalik 2. Structurally, the Main Frontal Thrust (MFT) divides the Terai Plain to the southern section and the Siwalik Group to the northern section. The Terai plain is subdivided into the Bhabar Zone and the Middle Terai in the studied section.Lithologically, the study area is characterized by sedimentary rocks, including siltstone, variegated mudstone, and fine-to coarse-grained sandstone. Features like the slickensides on sandstone, shear zones with many landslides, fault breccias, and sudden topographic breakages are field evidence to locate the MFT in the field. The sandstone in the Lower and the Middle Siwalik are classified as Feldspathic Wacke while those in the Upper Siwalik are as Lithic Arenite.